Efficacy of argon plasma coagulation in the management of portal hypertensive gastropathy - Hanafy, Amr Shaaban; El Hawary, Amr Talaat (Endoscopy International Open, 2016)
Objectives: Evaluation of the outcome and experience in 2 years of management of portal hypertensive gastropathy (PHG) by argon plasma coagulation (APC) in a cohort of Egyptian cirrhotic patients.Methods: This study was conducted over a 2-year period from January 2011 to February 2013. Upper gastrointestinal endoscopy was performed to evaluate the degree and site of PHG. APC was applied to areas with mucosal vascular lesions. Results: In total, 200 cirrhotic patients were enrolled; 12 patients were excluded due to death (n = 6) caused by hepatic encephalopathy (n = 3), hepatorenal syndrome (n = 2), or chronic lymphatic leukemia (n = 1), or did not complete the treatment sessions (n = 6), so 188 patients completed the study. PHG was mainly fundic in 73 patients (38.8 %), corporeal in 66 patients (35.1 %), and pangastric in 49 patients (26.1 %) (P = 0.026). Patients were exposed to APC and received proton pump inhibitors together with propranolol at a dose sufficient to reduce the heart rate by 25 % or down to 55 beats/min. The mean (± standard deviation) number of sessions was 1.65 ± 0.8; six patients needed four sessions (3.2 %), 19 patients needed three sessions (10.1 %), 74 patients needed two sessions (39.4 %), and 89 patients needed one session (47.3 %). Patients with fundic and corporeal PHG required the lowest number of sessions (P = 0.000). Patients were followed up every 2 months for up to 1 year; the end point was a complete response with improved anemia and blood transfusion requirement which was achieved after one session in 89 patients (75.4 %), two sessions in 24 patients (20.3 %) and three sessions in five patients (4.3 %). A complete response was more prevalent in patients with corporeal and fundic PHG (P = 0.04).Conclusions: After 2 years’ experience in managing PHG, we found that a combination of APC and non-selective beta blockers was highly efficacious and safe in controlling bleeding from PHG. In addition, APC alone is rapid, and effective in the control of PHG induced bleeding, especially when beta blockers are contraindicated.